High-Resolution Mapping of Subsurface Sedimentary Facies and Reservoirs Using Seismic Sedimentology - Hongliu Zeng (Applied Sciences)
This investigation presents the current status of seismic sedimentology, along with seismic geomorphology, as applied to the high-resolution (<5 m) mapping of sedimentary facies and hydrocarbon reservoirs in the subsurface. Seismic sedimentology involves the joint investigation of seismic lithology and seismic geomorphology. The high-resolution (as thin as one meter) interpretation of depositional units on lithofacies and paleo-landforms can be achieved by following a comprehensive workflow focusing on three mandatory steps (evaluating and improving data quality; selecting right attributes, preferably 90° seismic trace with frequency fusion; and making use of horizontal resolution on stratal slices) and two optional steps (guiding interpretation with seismic models and applying machine learning techniques). Seismic sedimentology is set to improve through enhanced calibration using well and outcrop data, along with regional and local geological models. Furthermore, there will be a deeper integration between geological and geophysical disciplines, as well as advancements in high-resolution geophysical acquisition and processing techniques.